Red cell membranopathies: Case series and review of literature - Ratna Sharma; Amit Jain (Elsevier, 2024)
Inherited disorders affecting the red blood cell (RBC) membrane result from mutations in membrane or skeletal proteins. Such mutations can impede red cell deformability, leading to a shortened lifespan and early removal of erythrocytes from circulation. This, in turn, results in anemia and jaundice. Hereditary spherocytosis (HS), hereditary elliptocytosis, hereditary ovalocytosis, and hereditary stomatocytosis are examples of these disorders, with HS being the most prevalent form of inherited hemolytic anemia. Disorders of the RBC membrane may stem from structural or transport functional changes, but they inevitably lead to clinical symptoms of hemolytic anemia. Accurate diagnosis is crucial to avoid complications or inappropriate treatment as management varies depending on pathophysiology. In this review, we describe few cases of different types of RBC membrane disorders with variable age of presentation, emphasizing the significance of correct approach, limitations of certain investigations and the need for genetic test to reach a precise diagnosis.